ANALISIS MORFOLOGI BAHASA DAYAK SAMIHIM DI DESA MANGKA KECAMATAN PAMUKAN BARAT KABUPATEN KOTABARU - Husni Mubarak (STKIP Paris Barantai, 2021)
The objectives of this study were (1) to describe the affixation process of the Dayak Samihim language. (2) Describe the process of reduplication of the Dayak Samihim language in Mangka Village. The method used in this research is a descriptive qualitative research method, which clearly describes the morphology of the Dayak samihim language in Mangka village, Pamukan Barat district, Kotabaru district. The data source was obtained from research sunjek, namely the indigenous Dayak people who live in the village of Mangka. Data collection techniques used are primary data and secondary data. The instruments in this study were guidelines, notebooks, laptops, cameras, and cellphones as recording devices. The research data is in the form of interviews with sources, field notes from observations related to this research. The sampling technique used in this research is probability sampling technique, simple random sampling model. The sample in this study is in the form of informants or sources. The population in this study was a population of 25 (two five) people who were selected based on the sample, then from the 25 (two five) people 18 (eighteen) people were selected as the research sample by the researcher. Keywords: Morphological Analysis, Dayak Language